Biocompatible Black Phosphorus Nanosheets-Antimicrobial Peptide Nanocomposites for Enhanced Anti-Infection Therapy - Shuo Liu; Zhishang Shi; Lin Teng; Junlian Nie; Libing Zhang (Molecules)
Bacterial infections are one of the major problems affecting human health, which is exacerbated by increasing antibiotic resistance. Antimicrobial peptides (AMPs) are an ideal alternative to antibiotics, but their instability and toxicity to mammalian cells need to be addressed. Here, black phosphorus nanosheets (BPs) were successfully decorated with melittin (Mel), a kind of AMP, through electrostatic interaction. The size impacts of BPs on the antibacterial ability and biocompatibility of BPs/Mel nanocomposites were studied systematically. Results showed that the nanocomposites made from middle-sized BPs (BPs/Mel-7) have strong antibacterial ability as well as good biocompatibility. Moreover, BPs/Mel-7 could accelerate skin wound healing infected by Staphylococcus aureus. This study provides a facile strategy to expand the application of AMPs.